The Influence Of Technology On Islamic Education In Indonesia - Idris Afandi (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Technology has had a significant impact on the world of education, including Islamic education in Indonesia. Through technology, access to sources of Islamic knowledge has become easier, especially with the existence of e-learning platforms, digital applications and social media. Technology also supports the teaching and learning process, accelerates the distribution of teaching materials, and increases interactivity between teachers and students. However, technology also presents challenges, such as dependence on digital devices and the potential for spreading information that is not in accordance with Islamic teachings. In the context of Islamic education, the importance of digital literacy becomes increasingly crucial to ensure that technology is used wisely and remains in line with Islamic values. This research aims to analyze the positive and negative impacts of implementing technology in Islamic education in Indonesia, as well as providing recommendations for educators and policy makers so that they can utilize technology optimally.